In Young Patients Undergoing Total Hip Arthroplasty, Is There a Correlation Between Activity Level and Wear of Highly Cross-Linked Polyethylene? - Sergio F. Guarin Perez, MD; Diego J. Restrepo, MD; Sheng-Hsun Lee, MD; Michael B. Stuart, MD; Robert T. Trousdale, MD; Daniel J. Berry, MD; Rafael J. Sierra, MD (JBJS Open Access)
Background:. Total hip arthroplasty (THA) effectively restores mobility, reduces pain, and enhances the quality of life of patients of all ages. Despite its benefits, concerns regarding the long-term effects of high-impact activities and sports on implant longevity require further study. This study investigated the effect of activity level on long-term radiographic wear of highly cross-linked polyethylene (HXLPE) in young patients undergoing THA. Methods:. Between 1999 and 2008, 785 patients (909 hips) aged ≤50 underwent primary THA using first-generation HXLPE liners from 4 different vendors with either metal or ceramic heads. Functional activity and participation questionnaires, including the Hip Injury and Osteoarthritis Outcome Score (HOOS Jr), University of California Los Angeles (UCLA) activity scale, and High-Activity Arthroplasty Score (HAAS), were surveyed in 2018 to 2019. The response rate was 44%. Radiographic linear wear rates were measured using the ROMAN software in patients who had completed questionnaires and had radiographs taken at least 10 years apart, leaving a final cohort of 249 patients (284 hips). Multivariate analyses were performed to determine the relationship between HXLPE wear rates and activity scores. Results:. At the time of the survey, approximately 10% of the patients performed high-impact activities not-recommended by consensus guidelines. The HXLPE linear wear rate was 0.036 mm/year (SD: 0.026). Patients with higher activity levels, as measured on the continuous UCLA/HAAS activity scale, did not exhibit increased wear (β = -0.0009; p = 0.31). Stair climbing was correlated with increased wear rates (β = 0.0066; p = 0.004), whereas walking (β = 0.0005; p = 0.66) and running (β = 0.0017; p = 0.30) were not significantly correlated. Patients performing nonrecommended activities did not show increased wear rates compared with those performing recommended activities (β = 0.0063; p = 0.19). Conclusions:. Linear wear rates of first-generation HXLPE were not related to functional activity or participation in high-impact activities. Future research should include longitudinal assessments of activity levels and data on other potential complications related to high-impact sports to provide robust evidence regarding recommended activity level postoperatively. Level of Evidence:. Level III, Retrospective Comparative Study. See Instructions for Authors for a complete description of levels of evidence.